Clinical and Embryological Characteristics of Infertility Treatment Cycles Using Fresh and Cryopreserved Testicular Spermatozoa - Panasovsky, Mykola (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(2): 199-202